Desenvolvimento e implementação de um software para análise tridimensional de edifícios altos em alvenaria estrutural - Kesio Palacio (2001)
This work deals with the implementation of pre- and postprocessor program, which is based on CAD, where uses a processing program named CEASO 01 [TORRES(1999)] to analyze tall buildings in masonry structures. The program CEASO 01 considers the use of thin-walled element of open cross section and space frame element to representthe groups of structural walls, beams with or without torsion strength to represent lintels, and slabs as rigid diaphragms. The thin-walled elements of open cross section, which represent the groups of structural walls with sectorial properties, are analyzed by using VLASSOVS (1961) bending and torsion theory, where are taken into account the warping and bimoment. This program also enables us to evaluate the effect of sheardeformation in the structural walls, considers the interaction among them, and elastic ground support for foundation by adding spring supports. The structural analysis is performed on first and second order effect. It uses the series sub-structuring technique, wherein the stiffness matrices and load vector of each floor are built and then they arecondensed into the coordinates of the inferior floor until it reaches the first floor ( base). It is presented three analyses of multistory buildings in structural masonry, where one compares the results of this proposed model of analysis for theses structures with those results obtained by finite-element method and the usual procedures.